Anti-aging potential and phytochemicals of Centella asiatica, Nelumbo nucifera, and Hibiscus sabdariffa extracts - Monsicha Khuanekkaphan; Chanai Noysang; Warachate Khobjai (Wolters Kluwer Medknow Publications, 2020)
Centella asiatica, Nelumbo nucifera Gaertn, and Hibiscus sabdariffa have been used as medicinal plants in Thailand. They are sources of phytochemicals that applications for esthetic and healthcare. The aim of this research was to examine the phytochemical constituents and anti-aging potential of these plants. The phytochemical compounds were performed using gas chromatography-mass spectrometry. The anti-aging activities were evaluated by 2,2-diphenyl-1-picrylhydrazyl (DPPH), 2,2'-azinobis (3-ethylbenzothiazoline-6-sunfonic acid) (ABTS), anti-collagenase, and anti-elastase assays. The main interest phytochemical compounds of ethanolic extracts of C. asiatica, N. nucifera, H. sabdariffa were ethanol, 2-(-Octadecenyloxy), γ-sitosterol and hexadecanoic acid, and ethyl ester, respectively. The DPPH half-maximal inhibitory concentration (IC50) results of C. asiatica, N. nucifera, and H. sabdariffa were 0.32 ± 0.01, 0.34 ± 0.00, and 0.35 ± 0.01 mg/mL, respectively. The ABTS result of H. sabdariffa extract showed high inhibitory activity at IC50of the extract was 0.62 ± 0.12 mg/mL. The percentage of collagenase inhibition of C. asiatica, N. nucifera, and H. sabdariffa at 1.0 mg/mL was 78.13 ± 4.42, 85.94 ± 2.21, and 90.63 ± 0.00, respectively. The C. asiatica extract had a high percentage of elastase inhibition. Consequently, these research results suggest that phytochemicals may also provide a range of esthetic and health benefits. The phytochemical constituent could be used as anti-aging active ingredient for cosmetic and pharmaceutical industrials.